Restrukturisasi Produk Pembiayaan Musharakah Mutanaqishah di Bank Syariah Indonesia dalam Perspektif Hukum Ekonomi Syariah - Munir Munir; Wahyu Hidayat; M. Ridwan Hambali; Ahmad Munir (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research is motivated by the demands of society for the Islamic banking industry to innovate and develop products and services in order to meet the needs and facilitate transactions. The purpose of this study is to describe the implementation of musha>rakah mutana>qisah financing products as a development of musha>rakah contracts. This study uses a field research methodology that is descriptive in nature. The research location is at the Bojonegoro Branch of the Indonesian Sharia Bank. This research was conducted using primary data sources obtained directly and secondary data sources obtained from other media such as books, journals and others. This study shows that the musha>rakah mutana>qisah contract has undergone restructuring, which should be intended for purchasing assets (houses, shop houses, motorcycles, cars and so on) but in its implementation, the object of musha>rakah mutana>qisah transactions between banks Indonesian sharia and customers are assets that are fully owned by customers, where previously the customer's assets were purchased in part by the bank to leave a portion of ownership (hissah) of one rupiah for the customer. So here applies the shirkah amla>k ikhtiyari contract in the form of joint ownership of assets. Then the bank's portion is acquired by the customer by purchasing it in installments according to the agreement until it is paid off and the asset is fully owned by the customer again. This is hilah/engineering in the contract that aims to get the customer to get cash. Therefore, it is more appropriate if the financing is carried out using an 'inah sale and purchase agreement, in which the customer sells his assets to the bank in cash, then the customer buys them again from the bank in installments according to the agreement. The law of buying and selling 'inah is permissible according to Syafiiyah scholars.